The Influence of Digital Storytelling on EFL Students’ Reading Motivation and Reading Habits - Yesi Darmayanti; Vivi Amanda; Rani Zahra; Asih Ria Ningsih; Khabib Muafi; Andini Safitri (Journal of English Language and Education, 2026)
This research examined the effect of digital storytelling on EFL students’ reading motivation and reading habits at SMK Inayah Ujung Batu. A quantitative approach with a quasi-experimental design was applied, involving an experimental group and a control group. The participants consisted of 40 second-grade students, divided equally into two classes: 20 students in the experimental class and 20 students in the control class. The experimental group received instruction through digital storytelling, whereas the control group was taught using conventional reading methods. Data were collected using Likert-scale questionnaires measuring reading motivation and reading habits. The data analysis employed descriptive statistics, paired sample t-tests, and independent sample t-tests using SPSS. The results demonstrated a substantial improvement in the experimental group. The mean score of reading motivation increased from 59.45 (pre-test) to 85.15 (post-test), while reading habits improved from 56.45 to 83.15. In comparison, the control group showed relatively lower gains. Statistical testing confirmed that the significance value was below 0.05 (Sig. = 0.000 0.05), indicating a statistically significant effect. These findings suggest that digital storytelling effectively enhances students’ motivation and fosters better reading habits. The integration of multimedia elements contributes to increased engagement, active participation, and positive attitudes toward reading. Therefore, digital storytelling can be considered an innovative and effective instructional medium for improving students’ reading-related outcomes in English language learning.